Peptide Fractions from Chymotrypsin-hydrolyzed Moringa oleifera Seed Proteins Inhibit α-amylase and α-glucosidase in vitro - Oluwafemi Emmanuel Ekun; Augustine Olusegun Olusola; Joseph Adaviruku Sanni; Feyisayo Ishola (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
This study attempts to investigate the activities of chymotrypsin-digested M. oleifera seed proteins and their peptide fractions on carbohydrate-hydrolyzing enzymes. Proteins from M. oleifera seeds were isolated using isoelectric point precipitation and hydrolyzed using chymotrypsin. The hydrolysates obtained were fractionated into peptide fractions of